General kinetic model framework for the interpretation of adiabatic calorimeter rate data - Bhattacharya, Arijit (Chemical Engineering Journal, 2005)
Notwithstanding the variety and complexity of the reactions studied by adiabatic calorimeters like ARC, the data interpretation techniques are not general enough. Traditional thermokinetic analysis primarily lumps a complex multi-step reaction into a single overall reaction and ignores possible thermal effects in some of the possible side reactions. With detailed chromatographic/mass spectrometric analysis of the headspace gases and the condensed phase residues, the pressure profile becomes an additional source of identification of the mechanism and the kinetics of the overall reaction. Finally, in the context of new multiphase catalytic processes of greater efficiency and environment friendliness and with reference to the storage of potentially incompatible fluid mixtures in metallic containers, ARC studies of heterogeneous reaction systems are becoming part of the mandatory safety evaluations. With a few additional measurements a proper kinetic interpretation of the ARC data on such systems seems possible. The paper presents a general model that was shown to be easily adaptable to a number of published reactions of various complexities referred to above. Standard thermal hazard characteristics like the onset temperature, adiabatic temperature rise, self-heat rate, time-to-maximum rate, pressure-temperature profile, etc. could be accurately calculated by the model and these compared closely with the experimental data. It is hoped that the model would be useful as a general-purpose tool for the interpretation of adiabatic calorimetric data for the purpose of process hazard assessment. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: accelerating rate calorimeters (ARC); Kinetic modeling; MOC (material of construction) incompatibility in storage; multi-step reactions; runaway reactions

General model for analyzing data on the rate of reactive dissolution of poly-disperse particulate solids - Bhattacharya, Arijit (Chemical Engineering Journal, 2008)
A model has been presented which successfully simulates the experimentally observed integral batch reactive dissolution rate data while accounting for the poly-dispersity of the solid particulate charge. This allowed avoiding arbitrary assumptions about the particulate inventory and size independence of the mass transfer coefficient. There is also no need for a priori identification of the controlling regime, which can change from kinetic to mass transfer during the process, apart from the possibility of the shift with the specified process and operating conditions. The model was applied with equal ease to a simple isothermal reaction, an exothermic reaction with runaway potential and to a phase-transfer catalysis reaction with a complex mechanism. The model was shown to predict the time required for a specified extent of conversion of the particulate reactant or the rate of consumption of a key liquid reactant under a variety of process and operating conditions, like temperature, liquid reactant and the catalyst concentration, particle size, poly-dispersity of the charge and agitation speed. Such information is useful in reactor design and scale-up. Where dissolution is accompanied with a runaway reaction, the model can predict quantities of interest in hazard assessment and should aid safe reactor design. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: kinetic model; particle size distribution; poly-disperse solid reactant; reactive dissolution; reactive thermal hazard; solid-liquid PTC reaction